Part 1: clinoptilolite-alumina-hydroxyapatite composites for biomedical engineering - OKTAR, FAİK NÜZHET; GÜNDÜZ, OĞUZHAN (AUSTRALIAN CERAMIC SOCIETY, 2017)
The preparation and characterization of bovine hydroxyapatite (BHA) and clinoptilolite alumina composites are studied. Clinoptilolite (Cp) and aluminium oxide (Al2O3) (at varying concentrations 5, 10 and 15 wt%) were added to calcinated BHA powder. Green cylindrical samples were sintered at several temperatures between 1000 and 1300 degrees C for 4 h in air. Compression strength, Vickers microhardness and elastic modulus, as well as density, were evaluated. Scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD) studies were also performed. The experimental results showed that varying concentrations 5, 10 and 15 wt% Cp-Al2O3 to BHA and difference in the sintering temperature between 1000 and 1300 degrees C increase in the microhardness (67 and 305 HV, respectively), compression strength (between 31 and 105.6 MPa, respectively) and elastic modulus (between 540 and 1275 MPa, respectively). The experimental results gained optimal parameters to be utilized in the preparation of BHA and Cp-Al2O3 composites. These natural Cp-Al2O3/BHA composites have the potential to be used in several advanced biomedical engineering applications.
Keywords: Bovine hydroxyapatite; Clinoptilolite; Alumina; Characterization; Biocomposites; MECHANICAL-PROPERTIES; COATINGS; GLASS; BIOCOMPATIBILITY; AL2O3; HA